Functional porous carboxymethylcellulose microspheres – preparation and reduction of hydrogen cyanide yield in cigarette smoke. (June 2015) - Sun, P. J.; Yang, S.; Sun, X. H.; Jia, Y. Z.; Wang, Y. P.; Wang, H. B.; Guo, J. W.; Nie, C.
<x content-type="archive" xml:space="preserve">Abstract</x> To selectively reduce the yield of hydrogen cyanide in cigarette smoke, porous carboxymethylcellulose microspheres were prepared through the sol–gel method. Cupric ions, the functional groups that have high complexing ability to hydrogen cyanide, were introduced to the carboxymethylcellulose microspheres during the sol–gel process. The microspheres were characterised using nitrogen adsorption and scanning electron microscopy. The microspheres have a predominantly macroporous structure indicating weak physisorption properties, but sufficient functional cupric ions groups to selectively adsorb hydrogen cyanide. With these carboxymethylcellulose microspheres as filter additives, the smoke yield of hydrogen cyanide could be reduced by up to 42%, indicating great potential of these microspheres as absorbents for removing hydrogen cyanide from cigarette smoke.